The relationship between morphology and impact toughness of poly(l-lactic acid)/poly(ethylene oxide) blends. (20th April 2015) - Li, Jin-Ze; Schultz, Jerold M.; Chan, Chi-Ming
Abstract: The morphology of unannealed and annealed poly(l -lactic acid)/poly(ethylene oxide) (PLLA/PEO) (80/20) and (50/50) blends were studied using polarized optical microscopy (POM), scanning electron microscopy (SEM) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). Samples were annealed at temperatures between 90 and 125 °C. The size of PLLA spherulites increased dramatically with annealing temperature. SEM analyses of the water-etched PLLA/PEO blend samples and ToF-SIMS analyses of the blend thin films indicated that the PEO content and thickness of the interspherulitic boundary region was higher in the (50/50) blend than in the (80/20) blend. The impact strength of the PLLA/PEO (80/20) blend was higher than that of the neat polymer for all preparation conditions, and for both the impact strength decreased with increasing crystallization temperature (and therefore also with increasing spherulite size). The impact strength of the (50/50) blend was always higher than those of the neat polymer and the (80/20) blend, and increased remarkably with crystallization temperature. The size of the PEO-rich domains within the spherulites was significantly larger in the (50/50) blend than in the (80/20) blend. The size of the intraspherulite PEO-rich domains, the size of the spherulites, and the width and PEO content of the boundary layer all acted to determine the impact toughness of the PLLA/PEO blends. It is suggested that the (50/50) blend exhibits this behavior because it could undergo plastic deformation within and between PLLA spherulites and sustain a higher level of stress in the interspherulitic regions. Graphical abstract: Highlights: Relationship between the morphology of PLLA /PEO blends and impact toughness (IT). IT of the PLLA/PEO (80/20) blend (A) decreased with crystallization temperature. IT of the PLLA/PEO (50/50) blend (B) increased with crystallization temperature. Increase in the IT of B is due to larger intraspherulitic PEO-rich domains. Increase in IT of B is also due to higher PEO conc. in the interspherulitic boundary.